Local culture as a corporate social responsibility multiplier: Confucian values' mediation between firm policies and employees' attitude. Issue 3 (22nd September 2020) - Chen, Jian-Yu; Lim, Suk-Jun; Nam, Hyun-Jung; Phillips, Joe
Abstract : Purpose: The Western-centric nature of research into corporate social responsibility (CSR) has left gaps in one's understanding of local culture's role in augmenting or undermining the impact of firms' CSR policies. This paper constructs and tests variables measuring "Confucian values" mediation between Chinese employees' perceived CSR and their job satisfaction, organizational commitment and organizational citizenship behavior. Design/methodology/approach: The hypotheses were tested through structural equation modeling, using data from 311 responses completed by employees at Chinese private companies, located in China's Cheng-Yu economic area (Chongqing and Chengdu). Findings: Chinese employees' perceived CSR had a positive significant effect on job attitudes (job satisfaction and organizational commitment). However, perceived CSR had no significant positive impact on organizational citizenship behavior. The authors also found that Confucian values are a partial mediator between perceived CSR and job attitudes and a full mediator between perceived CSR and organizational citizenship behavior. Originality/value: The results enrich one's understanding of cultural values in these relationships and suggest further research into how firms and governments in Confucian-based societies can better operationalize Confucian values to argument the firm's and country's CSR identity, thus improving job attitudes and public relations among customers who share this cultural heritage. For non-Confucian societies and foreign firms operating in China, the results encourage searches for Confucian value substitutes, such as trust and education, to incorporate into CSR mechanisms that promote these values among employees. The authors suggest approaches for furthering these agendas.